Enhanced Lipid Production in Chlamydomonas reinhardtii by Co-culturing With Azotobacter chroococcum - Xu, Lili; Cheng, Xianglong; Wang, Quanxi (Frontiers in Plant Science, 2018)
The green algae, Chlamydomonas reinhardtii, is one of the model species used to study lipid production, although research has focused on nitrogen-deficient cultures, that inhibit the development of biomass by C. reinhardtii and limit lipid production. In this study, Azotobacter chroococcum was added to the algal culture to improve lipid accumulation and productivity of C. reinhardtii. The maximum lipid content and production of C. reinhardtii in the co-culture were 65.85% and 387.76 mg/L, respectively, which were 2.3 and 5.9 times the control's levels of 29.11% and 65.99 mg/L, respectively. The maximum lipid productivity of C. reinhardtii in the co-culture was 141.86 mg/(L·day), which was 19.4 times the control's levels of 7.33 mg/(L·day). These increases were attributed to the enhanced growth and biomass and the change in the activity of enzymes related to lipid regulation (ACCase, DGAT, and PDAT). Compared to the conventional strategy of nitrogen deprivation, A. chroococcum added to the culture of C. reinhardtii resulted in higher lipid accumulation and activity, greater efficiency in the conversion of proteins to lipids, higher biomass, and increased growth of C. reinhardtii. Therefore, using A. chroococcum to improve the growth and biomass of C. reinhardtii is an efficient, rapid, and economically viable strategy for enhancing lipid production in C. reinhardtii.